2021
DOI: 10.3389/fcvm.2021.652761
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Vascular Disease—A State-of-the-Art Review

Abstract: Since the 1990s, there has been a steady increase in the number of cancer survivors to an estimated 17 million in 2019 in the US alone. Radiation therapy today is applied to a variety of malignancies and over 50% of cancer patients. The effects of ionizing radiation on cardiac structure and function, so-called radiation-induced heart disease (RIHD), have been extensively studied. We review the available published data on the mechanisms and manifestations of RIHD, with a focus on vascular disease, as well as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 129 publications
1
41
0
Order By: Relevance
“…Among these patients, 15% (17/115) had coronary artery disease and 9% (10/115) had carotid artery disease ( 35 ). A high prevalence of cardiovascular disease risk factors at HNC diagnosis requires personalized lifestyle changes and risk factor modifications to achieve LDL, blood pressure and blood sugar targets as early as possible ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, 15% (17/115) had coronary artery disease and 9% (10/115) had carotid artery disease ( 35 ). A high prevalence of cardiovascular disease risk factors at HNC diagnosis requires personalized lifestyle changes and risk factor modifications to achieve LDL, blood pressure and blood sugar targets as early as possible ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…At low doses, the damage was lessened by the activation of detoxification mechanisms, repair and turnover of damaged molecules, or through an increase in the cell proliferation that replaces irreparable or apoptotic cells. High doses were associated with irreversible damages [ 69 ]. Alterations in collagen synthesis by dysfunctional mesenchymal stem cells (MSCs) were linked to T cell large granular lymphocyte leukemia pathophysiology [ 70 ] and many preclinical animal studies showed that MSCs can enhance regeneration of tissues and accelerate angiogenesis and re-epithelialization [ 71 ], potentially via synthesis of extracellular vesicles [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, normal tissues are usually exposed or affected by RT, followed by induction of DNA damage, inflammatory responses and oxidative stress, leading to toxicity. This accounts for acute and long-term adverse effects seen with radiation treatment (4,38,39).…”
Section: Pathogenesismentioning
confidence: 99%
“…Accumulated evidence suggests that radiation-induced cardiovascular toxicity is a result of various mechanisms interacting with each other through multiple complex signaling pathways (4,38,39). Radiobiology research reveals that normal tissue injury is a dynamic and progressive process (59).…”
Section: Development Of Cardiovascular Toxicity After Rtmentioning
confidence: 99%